Risk factors for patellar tendinopathy in competitive volleyball players. Issue 6 (10th April 2011) - De Ridder, R; Mahieu, N; Reynaert, L; Poppe, W; Strubbe, K; Cools, A; Roosen, P
Abstract : Background: Patellar tendinopathy (PT) is an important problem in a volleyball population. However, in order to optimize rehabilitation and prevention strategies, not all intrinsic risk factors are known. This study is the first study that takes the hip strength into account. Objective: The objective is to identify some intrinsic risk factors of the lower limb for the development of PT in competitive volleyball players. Design: Retrospective. Setting: Eight male national volleyball teams participated in this study. Risk factors were assessed at the beginning of the season 2009–2010. By means of questionnaires, the participants injury history was documented. Participants: A total of 71 male players (25.1±4.5 years) were included. Players with a history of surgery and pain on the moment of testing were excluded. Assessment of risk factors: Muscle strength, muscle length and landing strategies were assessed. Main outcome measurements: The strength of the hip muscles was measured with a hand-held dynamometer. Muscle length of gastrocnemius, soleus, hamstrings and quadriceps was determined by means of a plurimeter. A 2D video analyses was made of a vertical jump. Knee flexion angle, Q-angle and Ankle dorsiflexion angle during the landing were calculated. Results: The players with a history of PT (>6 months ago) displayed a significant greater ankle dorsiflexion ROM, a significant lower hip flexion strength and a significant shorter quadriceps. A logistic regression model indicated that a greater ankle dorsiflexion ROM and a lower hip flexion strength are predictors for occurrence of PT. Conclusions: It can be concluded that a greater dorsiflexion ankle during landing and a lower hip flexion strength are associated with the occurrence of a PT. Future prospective studies should include, not only the knee, but also the hip and the ankle in their assessment.